The Effect of Sustainable Supply Chain Management on the Performance of Certified Organic Coffee at Malang Regency - Rosita Widya Putri; Dwi Retnoningsih (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2022)
This study aims to analyze the effect of sustainable supply chain management on the performance of organic Robusta coffee in the Farmers Group, Amadanom Village, Malang Regency. The impact of sustainable supply chain management in this study is identified from the supplier, manufacture, and consumer variables. Supply chain performance is known through economic, environmental, and social dimensions. The approach used in this research is quantitative. The data was collected from 50 respondents. These respondents are all elements of Farmer Group's sustainable supply chain. Sampling was done by census and snowball sampling. The research used the Structural Equation Modeling-Partial Least Square (SEM-PLS) method to analyze. This study showed that the supplier does not significantly affect economic performance but has a positive and significant impact on environmental performance and social performance. The manufacturing variable has a positive and significant effect on financial and social performance but does not substantially impact environmental performance. Consumers in a sustainable supply chain have a positive and significant effect on economic performance, environmental performance, and social performance.